Hepatoprotective Activity of Citrus Limetta on Wistar Albino Rats Hrishabh Jangid*, Mohammad Mukim, Rahul Ancheria, Ankit Sharma Kota College of Pharmacy, Kota, Rajasthan, India - Jangid, Hrishabh; Mukim, Mohammad; Ancheria, Rahul; Sharma, Ankit (Asian Journal of Pharmaceutical Research and Development, 2021)
The methanolic extract of citrus limetta (MECL) peel was screened for hepatoprotective activity in hepatotoxic wistar albino rats induced via paracetamol (PCM) and carbon tetra chloride (CCL4). Hepatoprotective activity of MECL was measured by estimating biochemical parameters such as AST (aspartate transaminase), ALT (alanine aminotransferase), SGPT (serum glutamine pyruvate transferase), SGOT (serum glutamic oxaloacetic transaminase). It was observed that administration of PCM, CCL4 decrease the level of proteins and increased the level of serum marker enzymes which is an evidence of existence of hepatotoxicity in rats. The present results provide strong evidence that MECL inhibits hepatotoxicity induced by CCL4 and PCM. The hepatoprotective action was much more significant at the dose of 2ml/kg when compared to 1mg/kg.